Financing regional development and competitiveness : problems and challenges at macro and micro level in Bulgaria - Tatjana Chubenova-Delisivkova (Revista română de economie, 2017)
The paper discusses the contemporary regional development of Bulgaria and regional financing by different national sources and European funds. The compliance with the EU requirements for attaining targeted results in specifically programmed priority areas is revealed as a driving force for improving the financial governance of regional development. The main tasks are to analyse the problems and prospects of the different types of regional development financing, their interdependence and overall impact on the regional production structures and social development. The issues of the efficiency and effectiveness of the decentralisation of public finances are analysed within the framework of the goals of sustainable regional development. By revealing the mechanisms and instruments of public financing the regional development some conclusions are made for the enhancement of fiscal coordination between the municipalities? and central Government authorities. The implementation of additional measures for more strict fiscal discipline at local level is considered with regard to improving the solvency of the municipalitiesbudgets and enhancing the capacity of the municipalities to manage their debts? repayment problems. Overcoming the shortage of municipalities'funding commitments and difficulties of meeting the obligations to serve due costs is discussed as an opportunity to improve the local finances. The role of public governance is revealed in order to consider the problems and future prospects for financing regional development. The methodology of the study involves the comparative analysis of the macro and micro financing of regional development and institutional and legal analysis of forms and schemes of public financing. In conclusion some problems and prospects are drawn for the public governance of Bulgaria in support of financing regional development.
2665773-9; 2344-4657; Revista română de economie; 717197875